2009
DOI: 10.5688/aj730222
|View full text |Cite
|
Sign up to set email alerts
|

Active-Learning Laboratory Session to Teach the Four M's of Diabetes Care

Abstract: Objective. To implement an active-learning methodology for teaching diabetes care to pharmacy students and evaluate its effectiveness. Design. Laboratory instruction was divided into 4 primary areas of diabetes care, referred to by the mnemonic, the 4 M's: meal planning, motion, medication, and monitoring. Students participated in skill-based learning laboratory stations and in simulated patient experiences. A pretest, retrospective pretest, and posttest were administered to measure improvements in students' k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Previous studies have examined the benefit of activelearning in increasing the understanding of classroom material and providing students a way to apply it to real-life situations. [14][15][16][17][18]23 These results, which were similar to ours, showed that providing supplementary courses and practice increases students' overall knowledge and confidence in performing practical skills. To our knowledge, this is the first study to determine that the effect of the diabetes training program on pharmacy students' self-confidence and attitudes toward diabetes care was different among students depending on their year in the curriculum.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Previous studies have examined the benefit of activelearning in increasing the understanding of classroom material and providing students a way to apply it to real-life situations. [14][15][16][17][18]23 These results, which were similar to ours, showed that providing supplementary courses and practice increases students' overall knowledge and confidence in performing practical skills. To our knowledge, this is the first study to determine that the effect of the diabetes training program on pharmacy students' self-confidence and attitudes toward diabetes care was different among students depending on their year in the curriculum.…”
Section: Discussionsupporting
confidence: 78%
“…The selfconfidence instrument used in this study was based on an existing instrument 12 and literature review. 2,3,[7][8][9][10][11][12][13][14][15] Four clinical faculty members from the Pharmacy Practice Department were asked to constitute an internal expert content panel to review for content, grammatical correctness, organization, readability, and clarity. They were also asked to share/suggest any additional items that were germane to self-confidence in providing diabetes care.…”
Section: Evaluation and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…7 By allowing students to apply their knowledge to simulated patient cases, students are able to increase their confidence before assisting actual patients. 5,6 This style of teaching is consistent with the ACPE standards which encourage faculty members to use active-learning strategies wherever possible to bridge the gap between the classroom and providing direct patient care. 6 The specific approach and assessment methods used for this study as well as outcomes are described.…”
Section: Introductionmentioning
confidence: 89%
“…When developing a method to provide additional immunization education and training, the course coordinators decided that the laboratory setting would be an excellent environment to provide hands-on training in a low-risk active-learning environment. 6 Active learning encourages students to process and understand information, which results in increased retention of information as opposed to learning solely by rote memorization. 7 Active-learning techniques may also help to ensure pharmacy students are able to "find, process, analyze and apply new information with their patients and their colleagues."…”
Section: Introductionmentioning
confidence: 99%